Конкурентоспроможність проектів у контексті теорії конкуренції - Романчик, Тетяна Володимирівна (НТУ "ХПІ", 2014)
В статті дістали подальшого розвитку теоретичні підходи до дефініції «конкурентоспроможність», висвітлено зміст категорії конкурентоспроможність проектів та обґрунтовано необхідність здійснення комплексної оцінки проектів у внутрішньому середовищі підприємства при обґрунтуванні оптимальності його товарної стратегії. Поширення теорії конкуренції на внутрішнє середовище підприємства дозволяє врахувати зацікавленість товаровиробника у розвитку окремих продуктів та сприяє виявленню його конкурентних переваг та потенційних можливостей.

In article got further development theoretical approaches to a definition "competitiveness", the content of category competitiveness of projects is reflected and need of implementation of a complex assessment of projects for the internal environment of the enterprise is proved at justification of an optimality of its commodity strategy. Distribution of the theory of the competition on the internal environment of the enterprise allows to consider interest of a producer in development of separate products and promotes detection of its competitive advantages and potential opportunities.
Competitiveness of projects in a context of the theory of competition
Keywords: діяльність підприємства; внутрішня конкурентоспроможність; асортиментна стратегія; чинники конкурентоспроможності; портфель проектів; комплексна оцінка; competitiveness of projects; internal competitiveness; assortment strategy; competitiveness factors; portfolio of projects; complex assessment